Ascorbate-Mediated Modulation of Cadmium Stress Responses: Reactive Oxygen Species and Redox Status in Brassica napus - Jung, Ha-il; Lee, Bok-Rye; Chae, Mi-Jin; Lee, Eun-Jin; Lee, Tae-Gu; Jung, Goo-Bok; Kim, Myung-Sook; Lee, Jinwook (Frontiers in Plant Science, 2020)
The role of ascorbate (AsA) in antioxidant defense system-associated resistance to cadmium (Cd) in oilseed rape plants has not yet been clearly demonstrated. The present study investigated the critical role of exogenous AsA on the physiological and biochemical responses of reactive oxygen species (ROS) and antioxidant scavenging defense systems in oilseed rape (Brassica napus L. cv. Tammi) seedlings exposed to Cd. Cd (10 µM) treatment led to significant reductions in plant growth; increases in the levels of superoxide anion radical, hydrogen peroxide, and malondialdehyde; and increases in Cd uptake and accumulation by the roots and shoots in hydroponically grown 10-day-old seedlings. Moreover, it reduced AsA content and AsA redox ratios, which have been correlated with reductions in glutathione (GSH) and/or nicotinamide adenine dinucleotide phosphate (NADPH) redox status. However, exogenously applying AsA to Cd-exposed seedlings decreased Cd-induced ROS, improved antioxidant defense systems by increasing AsA, GSH, and NADPH contents, and increased Cd uptake and accumulation in both roots and shoots of the plants. These results provided evidence that the enhancement in AsA redox status can be linked to an increase in the GSH and/or NADPH redox ratios through the induction of the AsA-GSH-NADPH cycle. Thus, these results suggest that exogenous AsA application to oilseed rape seedlings under Cd stress should alleviate the overall Cd toxicity by regulating the homeostasis of the AsA-GSH-NADPH cycle, which re-establishes the steady-state cellular redox status.